Thermal Environment and Cognitive Performance: Parameters and Equipment - Emília Rosa Quelhas Moreira Da Costa (2013)
The increasing complexity of work activities associated with different environmental conditions, can lead to a situation of thermal stress. The study of the respective impact on workplace has been gaining an increasing importance. It is therefore essential to identify and monitorize variables to evaluate the performance under different environmental conditions. This paper attempts to define the parameters and respective measurement equipment to study mental fatigue in different conditions of temperature and humidity. For such purpose, a literature review was carried out about different topics according to appropriate key words. From the results, it was possible to identify the most relevant parameters and the best suitable equipment for their measurement. It is hoped that the results may contribute to increased research in this field of study.